Persulfate enhanced electrochemical oxidation of highly toxic cyanide-containing organic wastewater using boron-doped diamond anode. (August 2020) - Yang, Wanlin; Liu, Guoshuai; Chen, Yinhao; Miao, Dongtian; Wei, Qiuping; Li, Haichao; Ma, Li; Zhou, Kechao; Liu, Libin; Yu, Zhiming
Abstract: Cyanide-containing organic wastewater is discharged in large quantities by coking, electroplating and pharmaceutical industries, which seriously endangers environmental safety and human health. In this paper, Electrochemical Oxidation-Persulfate (EO-PS) Advanced Oxidation Process (AOP) was firstly used to treat high concentration cyanide-containing organic wastewater obtained from a chemical enterprise. The potential application of this process in the treatment of high concentration cyanide-containing organic wastewater was explored for the first time, and the effects of current density, initial pH, temperature and initial concentration on chemical oxygen demand (COD), total organic carbon (TOC) and total cyanide (CN − ) removal in wastewater were systematically investigated. The results shown that the EO-PS process had an excellent removal effect on organics and cyanide in high concentration cyanide-containing organic wastewater which contained 11, 290 mg L −1 COD, 4456 mg L −1 TOC and 1280.15 mg L −1 CN − . The COD, TOC and CN − removal at optimized operating parameters for 24 h were 95.8%, 87.8% and 98.4%, respectively. The corresponding electrical energy per order was only 41.6 kWh m −3 order −1 . In addition, the pollutants removal can be accelerated under conditions of high current density, acidic solution, appropriate temperature and low pollutant concentration, among which low current density, low pH, appropriate temperature and low pollutant concentration can effectively diminish energy consumption. Cyanide, COD and TOC degradation in all reaction conditions followed the pseudo-first-order kinetic model. Highlights: EO-PS AOP was used to treat cyanide-containing organic wastewater. Organics and cyanide can be eliminated simultaneously at low energy consumption. Process parameters had a great impact on degradation efficiency. Cyanide, COD and TOC oxidation followed a pseudo-first-order kinetic.